Participação eletrônica, transparência e accountability no Gabinete Digital sob a lente da Teoria da Ação Comunicativa - Freitas, Jorge Lheureux de (2015)
Representative democracy is the government model that currently prevails in the Western world and has been showing signs of wear and demanding new solutions. With the strong and rapid advancement of technology, new ways of conducting social and business relationships are emerging. In state-owned area appears the electronic government, a kind of management that joins public administration with Information and Communication Technology, ICT. In this field, ICT enables three new modalities of communication between the society and government without mediators: e-participation, a virtual environment that allows people to opine on the state goals; transparency, which reveals to citizens what happens within the governments; and accountability, supported by ICT, which requires governments agents to account for its management. In order to better understand these three events it would be necessary to study a case with this focus. The chosen was the Digital Cabinet program, an initiative of Rio Grande do Sul’s state government, from 2011 to 2014, focused on these three expressions of e-government. The Theory of Communicative Action, TCA, has been chosen to interpret the phenomenon, due to its critical analysis of communicative and social action. From this combination of matters arose the research question: how do electronic participation, transparency and accountability express under the foundations of the Theory of Communicative Action in the Digital Cabinet? The qualitative research was found to be the best way to answer the question's challenge.The gathering of research information was enabled through semi-structured interviews addressed to four segments: politicians, large press corporations journalists and alternative media, interested in the program and team members of Digital Cabinet. In documentary research all the news published by the program were analyzed and categorized. The results showed when e-participation, transparency and accountability, as well as other events, expressed actions directed to understanding (communicative) or to success (strategic). Based on these findings the study suggests, for programs with similar characteristics and objectives of the Digital Cabinet, the most appropriate directions to follow and possible corrections routs or ones to avoid, in order to establish a relationship between the state and society based on the understanding, truth, sincerity and legitimized by values that represent the social environment.